THE EFFECT OF ECONOMIC GROWTH AND POVERTY ON INCOME INEQUALITY IN INDONESIA - Safrita Safrita; Tarmizi Abbas; Yurina Yurina (LPPM Universitas Malikussaleh, 2021)
This study aims to determine the impact of economic growth and poverty on income inequality in Indonesia. This study uses secondary data in the form of time series data from Indonesia's Central Bureau of Statistics. The data analysis method used is multiple linear regression methods using Eviews 9. Partial test results show that economic growth has a positive and significant impact on income inequality in Indonesia, and poverty has a negative and significant impact on income inequality. in Indonesia. At the same time, economic growth and poverty are positively affecting income inequality in Indonesia.